KOMPARASI MUAMALAH SYARIAH DAN MUAMALAH KONVENSIONAL - Miftahul Khaer; Risda B. Kulibang; Devi Azra Yunus; M. Amin; Muhammad Adnan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study examines the differences between Islamic muamalah and conventional muamalah in modern economic practices. The main issue addressed is the low level of public understanding of the principles and implementation of both systems. This study aims to compare Islamic and conventional muamalah in terms of principles, objectives, and implementation. The research employs a qualitative descriptive method using a literature review approach by analyzing books and academic references related to Islamic and conventional economics. The results indicate that Islamic muamalah is based on Islamic law derived from the Qur’an and Hadith, emphasizing justice and the prohibition of riba, gharar, and maysir, while conventional muamalah is oriented toward profit and market mechanisms. This study concludes that Islamic muamalah offers an ethical and just economic system.